2010
DOI: 10.1016/j.neuroscience.2009.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Topography and time course of changes in spinal neuropeptide Y immunoreactivity after spared nerve injury

Abstract: We used a new computer-assisted method to precisely localize and efficiently quantify increases in NPY immunoreactivity (NPY-ir) along the mediolateral axis of the L4 dorsal horn following transection of either the tibial and common peroneal nerves (thus sparing the sural branch, spared nerve injury, SNI), the tibial nerve, or the common peroneal and sural nerves. Two weeks after SNI, NPY-ir increased within the tibial and peroneal innervation territories; however, NPY-ir in the central-lateral region (innerva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
4
19
0
Order By: Relevance
“…It might be due to the different animal models used for the respective studies (complete Freund's adjuvant-induced inflammation versus surgical incision). Changes in NPY expression also occurs in neuropathic pain though this is mainly localized in the deeper laminae (Rexed's laminae III-IV), which is in accordance with changes in the large diameter dorsal root ganglion neurons instead of the smaller sized cell soma observed after inflammatory pain [14]. Paw incision-induced nociception was comprehensively attenuated up to day 2 by intrathecal administration of morphine, considered to be the gold standard reference drug for the treatment of pain in patients [34].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It might be due to the different animal models used for the respective studies (complete Freund's adjuvant-induced inflammation versus surgical incision). Changes in NPY expression also occurs in neuropathic pain though this is mainly localized in the deeper laminae (Rexed's laminae III-IV), which is in accordance with changes in the large diameter dorsal root ganglion neurons instead of the smaller sized cell soma observed after inflammatory pain [14]. Paw incision-induced nociception was comprehensively attenuated up to day 2 by intrathecal administration of morphine, considered to be the gold standard reference drug for the treatment of pain in patients [34].…”
Section: Discussionsupporting
confidence: 74%
“…However, expression of NPY in the spinal cord during the post-incision period was not studied. This could be important as definitive changes in NPY immunoreactivity was observed in specific sectors of the dorsal horn of the spinal cord after induction of neuropathic pain [14]. Consequently, the main objective of the present work was to characterize the temporospatial changes in the expression of NPY in the spinal cord of rats and to correlate this with post-incisional nociception.…”
Section: Introductionmentioning
confidence: 96%
“…When initiated before tissue or nerve injury, knockdown increased the intensity of thermal hypersensitivity and the duration of tactile hypersensitivity. Whether this reflects intrinsic NPY-mediated attenuation of the development of hypersensitivity is unclear, in part because NPY expression studies have not reported changes before 3 or 14 d after inflammation (7) or nerve injury (3,8,9,28), respectively. When initiated after injury, knockdown produced a rapid, reversible, and repeatable increase in hypersensitivity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nerve injury elicits a profound de novo synthesis of NPY in large-diameter neurons of dorsal root ganglion (DRG) and their terminal regions in the dorsal horn (3)(4)(5)(6)(7), perhaps serving as an adaptive compensatory response to increased excitatory signaling (8). Increases in NPY last at least 24 wk, indicating that it is temporally available to confer long-lasting inhibition of pronociceptive neurotransmission (9), but this hypothesis has not been tested.…”
mentioning
confidence: 99%
“…These stimuli are unique in that they fail to evoke a nocifensive response prior to injury [6]. Tactile or mechanical hyperalgesia is frequently measured as an exaggeration of the animal's nocifensive response to noxious stimuli, such as the pricking of the skin with sharp needle points [7]. Because the stimuli used are sufficient to exceed the pain threshold (PT) before the injury, pinprick stimuli are specific to the detection of mechanical hyperalgesia and analgesia and are not suited to the detection of allodynia or to the detection of the baseline PT.…”
Section: Introductionmentioning
confidence: 99%